Services Trade Liberalization and Regulatory Reform : Re-invigorating International Cooperation - Hoekman, Bernard (2012)
Trade and investment in services are inhibited by a range of policy restrictions, but the best offers so far in the Doha negotiations are on average twice as restrictive as actual policy. They will generate no additional market opening. Regulatory concerns help explain the limited progress. This paper develops two proposals to enhance the prospects for both liberalization of services trade and regulatory reform. The first is for governments to create mechanisms ("services knowledge platforms") to bring together regulators, trade officials, and stakeholders to discuss services regulatory reform. Such mechanisms could identify reform priorities and opportunities for utilization of "aid for trade" resources, thereby putting in place the preconditions for future market opening. The second proposal is for a new approach to negotiations in the World Trade Organization, with a critical mass of countries that account for the bulk of services production agreeing to lock-in applied levels of protection and pre-committing to reform of policies affecting foreign direct investment and international movement for individual service providers -- two areas where current policy is most restrictive and potential benefits from liberalization are greatest. If these proposals cannot be fully implemented in the Doha time frame, then any Doha agreement could at least lay the basis for a forward-looking program of international cooperation along the proposed lines.